A Semitransparent Inorganic Perovskite Film for Overcoming Ultraviolet Light Instability of Organic Solar Cells and Achieving 14.03% Efficiency - Chen, Weijie; Zhang, Jingwen; Xu, Guiying; Xue, Rongming; Li, Yaowen; Zhou, Yinhua; Hou, Jianhui; Li, Yongfang (Advanced materials (Weinheim), 2018)
Organic solar cells (OSCs) can be unstable under ultraviolet (UV) irradiation. To address this issue and enhance the power conversion efficiency (PCE), an inorganic‐perovskite/organic four‐terminal tandem solar cell (TSC) based on a semitransparent inorganic CsPbBr3 perovskite solar cell (pero‐SC) as the top cell and an OSC as bottom cell is constructed. The high‐quality CsPbBr3 photoactive layer of the planar pero‐SC is prepared with a dual‐source vacuum coevaporation method, using stoichiometric precursors of CsBr and PbBr2 with a low evaporation rate. The resultant opaque planar pero‐SC exhibits an ultrahigh open‐circuit voltage of 1.44 V and the highest reported PCE of 7.78% for a CsPbBr3‐based planar pero‐SC. Importantly, the devices show no degradation after 120 h UV light illumination. The related semitransparent pero‐SC can almost completely filter UV light and well maintain photovoltaic performance; it additionally shows an extremely high average visible transmittance. When it is used to construct a TSC, the top pero‐SC acting as a UV filter can utilize UV light for photoelectric conversion, avoiding the instability problem of UV light on the bottom OSC that can meet the industrial standards of UV‐light stability for solar cells, and leading to the highest reported PCE of 14.03% for the inorganic‐perovskite/organic TSC. A wide‐bandgap and low‐defect‐concentration CsPbBr3 film is fabricated using the vacuum‐evaporation method, and the related solar cell shows a high efficiency and robust photostability. When constructing inorganic‐perovskite/organic tandem solar cells, the top CsPbBr3‐based semitransparent perovskite solar cells can be used to filter ultraviolet (UV) light and overcome the UV‐light stability problem of the organic solar cells; they also show a record efficiency of 14.03%.